Opinião de pesquisadores e dirigentes sobre a importância da informação especializada: o caso da Embrapa - Maria Alice Bianchi (1991)
The present study was conducted at , the BrasilianAgricultural Research Coorporation (Empresa Brasileira de Pesquisa Agropecuária - EMBRAPA), and it investigated how well information used by researchers in their work is perceived by them and by research raanagers. The relationship between the researchers, perception of the information and their interest in the infrastucture of the Information and documentation Sectors (Setores de lnformação e Documentação· STDs) was also investigated. By using the less·structured interview, 28 researchers and eight managers were interviewd. ln a general way,information was consiclered very important for the researcher work. The relationship between the use of information and the generation of technology was established by most of the respondents, as well as the interest in tlie infrastucture of lnformation and Documentation Sectors (STDs) was e pressed. Important observations were macle by researchers on the managers behavior concerning information. These observations may work as an additional data for the managers evaluation services.